1987
DOI: 10.1044/jshr.3001.105
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Modeling and Imitation Teaching Procedures on Children with and without Specific Language Impairment

Abstract: Following a treatment program in which an invented morpheme was taught through either imitation or modeling procedures, the generalization of 40 specific language-impaired children was compared to that of 40 children learning language normally. The results of the comparison indicated that the two teaching procedures have opposite relative effects on the two groups. The abnormal group generalized more extensively following imitation teaching while the normal group generalized more extensively following modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
5

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 0 publications
2
40
0
5
Order By: Relevance
“…First, the original assumption that one procedure would be found to be superior to all others will have to be revised. The results as a whole suggest that all of these procedures are useful in particular situations depending on the purpose [24,25], the modality [22,23] and the characteristics of the children [21]. At this point, it may be more appropriate to ask a more complicated question than the one originally posed.…”
Section: Intervention Research: Proceduresmentioning
confidence: 91%
See 3 more Smart Citations
“…First, the original assumption that one procedure would be found to be superior to all others will have to be revised. The results as a whole suggest that all of these procedures are useful in particular situations depending on the purpose [24,25], the modality [22,23] and the characteristics of the children [21]. At this point, it may be more appropriate to ask a more complicated question than the one originally posed.…”
Section: Intervention Research: Proceduresmentioning
confidence: 91%
“…The results indicated that there were no differences between the treatment groups regardless of teaching method. Analyses of possible interactions between treatment methods and children's developmental levels within this study and others [22][23][24][25][29][30][31] suggest that there may be interactions between treatment method and subject characteristics such as language and cognitive level. Given the definitional differences across studies and the incompleteness of some of the subject information provided it is difficult to determine the nature of those interactions.…”
Section: Intervention Research: Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Modeling is a technique that is often used by therapists to promote communicative competence (Camarata & Nelson, 1992;Camarata, Nelson, & Camarata, 1994;Connell, 1987;Hart & Risley, 1985;Norris & Hoffman, 1990). When used in language instruction, modeling refers to the provision of appropriate examples of target sounds, words, or phrases.…”
Section: Modelingmentioning
confidence: 98%